Odpowiedzi

Najlepsza Odpowiedź!
2010-01-12T19:29:43+01:00
A)
3x+y=13
2x-y=7

y = 13-3x
2x - (13 - 3x) = 7
2x - 13 + 3x = 7
5x = 20 |:5
x = 4

y = 13 - 3x
y = 13 - 3*4 = 13-12
y = 1



b)
x+y=4
x+2y=6

x = 4 - y
(4 - y) + 2y = 6
4 - y + 2y = 6
y = 6-4
y = 2

x = 4 - 2
x = 2
2010-01-12T19:30:38+01:00
A)
3x+y=13
2x-y=7

y=13-3x
2x-(13-3x)=7

y=13-3x
2x-13+3x=7

y=13-3x
5x=20 |:5

y=13-3x
x=4

y=13-12=1


b)
x+y=4
x+2y=6

x=4-y
4-y+2y=6

x=4-y
y=6-4

x=4-y
y=2

x=2
2010-01-12T19:33:17+01:00
A)
3x+y=13
2x-y=7
+
---------
5x=20/:5
x=4

-y=7-2x
x=4

-y=7-8
-y=-1/:(-1)
y=1

x=4
y=1


b)
x+y=4
x+2y=6

y=4-x
x+2y=6

podstawiamy w drugim wyrażeniu pod y tą wartość z pierwszego wyrażenia:
x+2•(4-x)=6
x+8-2x=6
-x=-2/:(-1)
x=2

y=4-x
x=2

y=4-2
y=2

x=2
y=2